Dupe Culture in Intellectual Property Law: Between Consumer Expression and Trademark Infringement - Naila Aulia Rahmah Virhanida; Nazwa Rahmannina Rustandi; Putri Nur Wisudawati; Nesya Salwa Nurfadhilah (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2025)
The phenomenon of dupe culture—the trend of purchasing imitation products—has emerged as a growing consumer behaviour, particularly among younger, urban populartions seeking access to premium lifestyles at affordable prices. While economically viewed as a form of market inclusivity, this practice presents complex legal dilemmas, especially in the realm of Intellectual Property Rights (IPR) and trademark protection. This article critically examines how dupe culture operates within the blurred lines between inspired innovation and trademark infringement, and how Indonesian regulations respond to this challenge. Employing a normative and comparative legal approach, the study analyses regulatory gaps in trademark law and evaluates potential solutions, including ethical dupe certification, industry licensing collaborations, and consumer education. The findings suggest that an adaptive, participatory legal framework grounded in public literacy is essential to restructure duplicative practices in a way that safeguards creators' rights without stifling market dynamics. Consequently, dupe culture should not be viewed solely as a threat, but as an opportunity for IPR reform and the strengthening of the national creative industry ecosystem.